Water column particulate matter: A key contributor to phosphorus regeneration in a coastal eutrophic environment, the Chesapeake Bay. Issue 4 (11th April 2017) - Li, Jiying; Reardon, Patrick; McKinley, James P.; Joshi, Sunendra R.; Bai, Yuge; Bear, Kristi; Jaisi, Deb P.
Abstract: Particulate phosphorus (PP) in the water column is an essential component of phosphorus (P) cycling in the Chesapeake Bay because P often limits primary productivity, yet its composition and transformation remain undercharacterized. To understand the mobilization of PP and P sequestration in the water column, we studied seasonal variations in particulate organic and inorganic P species at three sites in the Chesapeake Bay, using chemical extractions, 1‐D ( 31 P) and 2‐D ( 1 H‐ 31 P) NMR spectroscopies, and electron microprobe analyses. Our results suggest that an average of 9% and 50% of water column PP was recycled in shallow and deep sites, respectively, primarily through remineralization of organic P, which was 3 times higher than Fe‐bound P remobilization. P recycling efficiency was highest in the warm and anoxic seasons. Organic P compositions and concentrations responded strongly to seasonal and redox variations: orthophosphate monoesters and diesters, and diester‐to‐monoester ratios (D/M) decreased with depth; both esters and D/M ratios were lower in the anoxic waters in July and September. In contrast, pyrophosphate concentration increased with depth and polyphosphate concentration was high in anoxic seasons. Our analyses suggest the presence of Ca‐phosphate minerals (Ca‐P) in the water column but with concentrations comparable to sediment Ca‐P. It is unclear, however, whether authigenic precipitation occurred in the water column or resuspended from sediments. Overall, these results reveal the dominance of internal P cycling particularly via organic P remineralization and controlling P availability in the water column of the Chesapeake Bay. Key Points: Particulate organic P remineralization is a significant source of dissolved P in the water column of the Chesapeake Bay The composition and transformation of particulate organic P responds strongly to seasonal and redox conditions Authigenic precipitation of calcium phosphate is speculated in the P‐rich hypoxic water column